The Efficacy of Literacy Teaching Reading: How Can Students' Extrinsic and Intrinsic Motivation and Reading Comprehension Proficiency Be Increased by Game-Based Learning with Kahoot? - anningrum, mustaniroh; Frimadhona Syafri (English Education Journal, 2023)
This study intended to determine whether game-based learning with Kahoot may enhance students' intrinsic and extrinsic motivation for reading comprehension. The objectives of the study were: (1) to show the effectiveness of game-based learning using Kahoot to improve extrinsic and intrinsic motivation. (2) to demonstrate the effectiveness of game-based learning using Kahoot in reading comprehension. (3) to show the relationship among the game-based learning using Kahoot, extrinsic and intrinsic motivation, and reading comprehension. The aim of the study was to teach students in Walisongo Senior High School Pecangaan's XI Kesehatan class learning for reading analytical exposition texts. The test, observation sheet, and questionnaire sheet were the instruments employed. The study's conclusions demonstrated the effectiveness of game-based learning with Kahoot in improving students' reading comprehension extrinsic and intrinsic motivation. The post-test results showed that the students' post-test after utilizing Kahoot was greater than the students' pretest before to receiving the treatment. Pre- and post-test results indicated a significant difference in students' motivation. It suggested that there was significant effect of using Kahoot to improve students’ extrinsic and intrinsic motivation and it revealed a link between Kahoot and students' extrinsic and intrinsic motivation, and reading comprehension.